Evolution of biocarbon strength and structure during gasification in CO2 containing gas atmosphere - Aki Koskela; Hannu Suopajärvi; Juha Uusitalo; Timo Fabritius (Fuel Communications, 2023)
This work focuses on the properties of hydrolysis lignin biocarbons with a perspective on utilizing the biocarbons in pyrometallurgical processes. Even if the blast furnace and basic oxygen furnace (BF-BOF) process route was replaced by emerging technologies with lower CO2 emissions in the future, the need for carbonaceous materials in the iron and steel making industry will still exist. Most of these applications do not require as high standards for the properties of carbonaceous materials as BF but the requirements are still similar to those for BF. The most important properties of carbonaceous materials are the mechanical strength and suitable reactivity. In the case of biocarbon, the apparent density is also considered important. The reactivity and strength properties are investigated with isothermal reactivity tests and compression strength tests for the non-gasified and pre-gasified biocarbon and reference coke samples. The mass loss rate of coke gasification (-0.069%/min) was considerably lower than that of least reactive biocarbon L1200 (-0.18%/min). Regarding the compression strength of the samples, the strength of coke dropped by 56.44% for the samples of pre-gasification level of 50% compared to non-gasified samples while the drop was only 40.68% for the L1200 biocarbon samples. The level of gasification was found to have direct correlation with pore area percentage with R2 value 0.92 in case of L1200 and 0.98 in case of coke. Further, the pore area percentage correlated with the compression strength with R2 of 0.93 in case of L1200 and 0.98 in case of coke.